2017
DOI: 10.3390/ijms18081615
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling in Endothelial Cells: Is It the Therapeutic Target for Vascular Neointimal Hyperplasia?

Abstract: Blood vessels respond to injury through a healing process that includes neointimal hyperplasia. The vascular endothelium is a monolayer of cells that separates the outer vascular wall from the inner circulating blood. The disruption and exposure of endothelial cells (ECs) to subintimal components initiate the neointimal formation. ECs not only act as a highly selective barrier to prevent early pathological changes of neointimal hyperplasia, but also synthesize and release molecules to maintain vascular homeost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 105 publications
0
36
0
Order By: Relevance
“…Mammals express four Notch transmembrane receptors (Notch-1, Notch-2, Notch-3, and Notch-4) and five typical transmembrane ligands (Delta-like 1 [Dll-1], Dll-3, Dll-4, Jagged-1, and Jagged-2). As mentioned, different combinations of Notch receptors and their ligands can play different roles in EC behavior [1]. Noseda et al [16] provided the first evidence that Notch activation in ECs results in morphological, phenotypic, and functional changes and induces the EndMT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mammals express four Notch transmembrane receptors (Notch-1, Notch-2, Notch-3, and Notch-4) and five typical transmembrane ligands (Delta-like 1 [Dll-1], Dll-3, Dll-4, Jagged-1, and Jagged-2). As mentioned, different combinations of Notch receptors and their ligands can play different roles in EC behavior [1]. Noseda et al [16] provided the first evidence that Notch activation in ECs results in morphological, phenotypic, and functional changes and induces the EndMT.…”
Section: Discussionmentioning
confidence: 99%
“…The damage to ECs initiates the development of neointimal hyperplasia and endothelial regeneration occurs to restore the protective barrier at the end of the neointimal hyperplasia [18]. In addition, VSMC proliferation and migration are common characteristics of neointimal hyperplasia; ECs also contribute to neointimal hyperplasia as a source of smooth muscle-like cells [1]. We and others have previously shown that ECs can acquire a fibro-proliferative mesenchymal phenotype through the EndMT under pathological conditions [3,6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Notch signalling may direct lesion formation by modulating the function of EC, SMCs, macrophages and stem cells [31][32][33][34][35][36] .…”
Section: Tgf-β1 Is Released By Both Inflammatory Cells and Vascular Cmentioning
confidence: 99%